Hidden men: Bearing witness to mandatory detention in Australia - Fleay, Caroline; Briskman, Linda (Oxford University press, 2013)
The Australian Government policy of mandatory immigration detention has been the subject of critique by human rights bodies and civil society. With many immigration detention facilities being located in remote sites, distance and expense means that few people get to observe detention practices in Australia directly. Through direct observations and through the voices of three men detained in the Curtin Immigration Detention Centre outside of the remote Western Australian town of Derby, the human costs of mandatory detention are presented and discussed. This is done through positioning this discussion as part of the process of bearing witness to mandatory detention in Australia.